G-quadruplexes and their ligands - Santos, Tiago (2021)
Funding Information: (PD/00065/2013). This work was supported by PESSOA program ref. 5079 and project “Projeto de Investigação Exploratória” ref. IF/00959/2015 entitled “NCL targeting by G-quadruplex aptamers for cervical cancer therapy” financed by Fundo Social Europeu e Programa Operacional Potencial Humano. Thanks are due to FCT/MCT for the financial support of the CICS-UBI UIDB/00709/2020 research unit and to the Portuguese NMR Network (ROTEIRO/0031/2013-PINFRA/22161/2016), through national funds and, where applicable, supported by European Investment Funds FEDER through COMPETE 2020, POCI, PORL and PIDDAC.